Epidermolysis bullosa dystrophica. From clinics to genetics - Sobczyńska-Tomaszewska, Agnieszka; Wertheim, Katarzyna; Kowalewski, Cezary; Kutkowska-Kaźmierczak, Anna; Woźniak, Katarzyna; Bal, Jerzy (Dermatology Review/Przegląd Dermatologiczny, 2009)
Epidermolysis bullosa dystrophica belongs to a group of genetically determined skin disorders (Epidermolysis bullosa hereditaria) and is caused by mutations in the COL7A1 gene encoding collagen VII. Production of collagen VII with altered physical and chemical properties, or lack of its synthesis, leads to disruption of anchoring fibrils and formation of blisters below the level of the lamina densa. Clinical features of the disease vary from mild, localised skin disorders to severe, generalised disease with poor prognosis. Epidermolysis bullosa dystrophica phenotype as well as inheritance pattern (autosomal dominant or recessive) depend on type of mutation and its localisation in the COL7A1 gene. There are now more than 320 mutations known in the COL7A1 gene. In this paper we present current knowledge about the clinical, therapeutic and genetic aspects of Epidermolysis bullosa dystrophica.